OcomCSP12, a Chemosensory Protein Expressed Specifically by Ovary, Mediates Reproduction in Ophraella communa (Coleoptera: Chrysomelidae) - Ma, Chao; Cui, Shaowei; Tian, Zhenya; Zhang, Yan; Chen, Guangmei; Gao, Xuyuan; Tian, Zhenqi; Chen, Hongsong; Guo, Jianying; Zhou, Zhongshi (Frontiers in Physiology, 2019)
Chemosensory proteins (CSPs) are considered to be the transporter linking odorant chemicals and receptors on sensory neurons. However, extensive expression patterns of CSPs in insects suggest that CSPs are also involved in other physiological processes, but the range of their functions remains uncertain. In this study, we successfully characterized and cloned the CSP12 of Ophraella communa (OcomCSP12). The open reading frame of OcomCSP12 encodes 131 amino acids, with four conserved cysteine residues. The expression patterns of OcomCSP12 validated by quantitative real time PCR (qRT-PCR) showed that OcomCSP12 is specifically expressed in female ovary. Furthermore, compared with the control treatment, silencing OcomCSP12 resulted in significantly reduced oviposition in females. Surprisingly, the knock down rate of OcomCSP12 exceeded 95% and remained depressed more than 15 days, indicating RNA interference (RNAi) was a suitable method to explore the function of CSP12 in O. communa. These findings increase our understanding of the expression profile and function of the CSP gene family in insects.